2002
DOI: 10.1056/nejmoa020841
|View full text |Cite
|
Sign up to set email alerts
|

Two Patients with Unusual Forms of Varicella–Zoster Virus Vasculopathy

Abstract: NFECTION of cerebral arteries by varicellazoster virus (VZV) can produce unifocal or multifocal vasculopathy. Unifocal large-vessel vasculopathy (granulomatous arteritis) usually affects elderly immunocompetent persons, whereas multifocal vasculopathy occurs primarily in persons who are immunocompromised. 1 Unifocal large-vessel infarcts may follow zoster in a trigeminal distribution and are presumed to result from transaxonal transport of virus from trigeminal afferent fibers that innervate vessels of the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
84
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 17 publications
9
84
1
Order By: Relevance
“…7,26,27 Similarly, we found that the overall risk for having a stroke increased in patients with herpes zoster. The pathomechanisms explaining this phenomenon are still unknown; however, there is some speculation that it involves the dissemination or cooccurrence of viral reactivation in cerebral ganglia spreading to the supplying vessels.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…7,26,27 Similarly, we found that the overall risk for having a stroke increased in patients with herpes zoster. The pathomechanisms explaining this phenomenon are still unknown; however, there is some speculation that it involves the dissemination or cooccurrence of viral reactivation in cerebral ganglia spreading to the supplying vessels.…”
Section: Discussionsupporting
confidence: 64%
“…6 It is hypothesized to spread along the nerve fibers to the blood vessels where it induces further inflammatory and thrombotic responses. 2,7,8 Two major spectrums of VZV vasculopathy have been identified: large-and small-vessel VZV vasculopathy. 9 In large-vessel VZV vasculopathy, the involved vessels are damaged by virus-induced inflammation, 2 presented as granulomatous angiitis in pathology, and can result in stroke.…”
mentioning
confidence: 99%
“…2,3 This possibility is supported by findings from a Taiwanese population study showing a 30% increase in the …”
Section: Resultsmentioning
confidence: 65%
“…2 Similar pathology has also been found in strokes and TIA, which follow HZ occurring at nonophthalmic sites and even in the absence of rash, raising the possibility that VZV is more widely implicated in the pathogenesis of cerebrovascular disease. 2,3 This possibility is supported by findings from a Taiwanese population study showing a 30% increase in the incidence of stroke for up to a year after acute HZ, and a 4.5-fold increase after HZ ophthalmicus (HZO). 4,5 Herein, we analyze the risk of stroke and TIA after HZ in a large retrospective UK population-based matched cohort study followed for up to 24 years (median 6.3 years).…”
mentioning
confidence: 86%
“…3 Single episode or recurrent ischaemic strokes have been recorded in infants and the elderly and may respond to treatment with acyclovir. 5 We report here on a female aged 2 years 6 months with a right cerebral hemisphere multifocal VZV-small-vessel vasculopathy. The child suffered from recurrent strokes triggered by intercurrent viral upper respiratory tract infections (URTI), until treatment was started with acyclovir.…”
mentioning
confidence: 90%